(untitled) (Journal of Hama University, 2019)
The computer has become an integral part of our lives and working places. This includes the discipline of architecture from the initial stage of conceptual design to its final virtual representation. The use of Computer-Aided Design (CAD) has revolutionized how architecture is practiced and thus it was necessary to rethink the process of architectural design and its presumptions and develop a new vision of architecture. Various CAD programs have been developed as powerful tools in design making process and helped architects to achieve possible optimal solutions. This research examines the essential role of Computer-Aided Design, its potential and its contribution to architecture. Then, it introduces few examples of modern buildings that were designed using the most advanced CAD software in order to explain their potentials and their ability to save time and efforts.